Features of respiratory rehabilitation in children after COVID-19 according to Ukrainian and global guidelines - Yu.V. Marushko; O.V. Khomych (Zdorovʹe Rebenka, 2025)
Background. With the spread of coronavirus disease 2019 (COVID-19) among children, study of its consequences and the need for effective rehabilitation methods following recovery have become important issues. Given an increasing number of post-COVID complications in pediatric practice, the development and implementation of scientifically grounded approaches to respiratory rehabilitation are crucial. The purpose of this article is to summarize current scientific data presented in publications from the PubMed, Scopus, and Web of Science databases, as well as in international and national clinical guidelines regarding the features of respiratory rehabilitation in children after COVID-19. Results. Respiratory rehabilitation of children after COVID-19 is critically important due to potential long-term consequences for the respiratory system, including shortness of breath, cough, and reduced physical endurance. Given the growing number of COVID-19 cases among children, it is necessary to implement effective rehabilitation methods that meet modern requirements and contribute to the complete recovery of respiratory functions. Conclusions. Respiratory rehabilitation of children after COVID-19 is essential for restoring respiratory functions and reducing symptoms. An individualized approach to respiratory rehabilitation allows for consideration of the age and physiological characteristics of each child. This enables the adaptation of rehabilitation methods to achieve maximum effectiveness during the recovery process. Further research will allow for a detailed evaluation of the effectiveness of various rehabilitation approaches, including physical exercises, breathing techniques, and psychological support, in children after COVID-19. It will also help identify optimal treatment strategies depending on the severity of the disease and the individual characteristics of patients.